2016
DOI: 10.1186/s12864-016-3006-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide recruitment profiling of transcription factor Crz1 in response to high pH stress

Abstract: BackgroundExposure of the budding Saccharomyces cerevisiae to an alkaline environment produces a robust transcriptional response involving hundreds of genes. Part of this response is triggered by an almost immediate burst of calcium that activates the Ser/Thr protein phosphatase calcineurin. Activated calcineurin dephosphorylates the transcription factor (TF) Crz1, which moves to the nucleus and binds to calcineurin/Crz1 responsive gene promoters. In this work we present a genome-wide study of the binding of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Actually, the ENA1 promoter is one of the strongest Crz1 recruiters upon high pH stress (Petrezsélyová et al, ), reaching a peak between 2 and 5 min after shifting to pH 8.0. This fast kinetics is in accordance with the almost instantaneous cytosolic calcium peak (Viladevall et al, ), which is followed by a very quick Crz1 entry (1–2 min) into the nucleus (Petrezsélyová et al, ; Roque, Petrezsélyová, Serra‐Cardona, & Ariño, ).…”
Section: The Ena Efflux Systemsupporting
confidence: 70%
“…Actually, the ENA1 promoter is one of the strongest Crz1 recruiters upon high pH stress (Petrezsélyová et al, ), reaching a peak between 2 and 5 min after shifting to pH 8.0. This fast kinetics is in accordance with the almost instantaneous cytosolic calcium peak (Viladevall et al, ), which is followed by a very quick Crz1 entry (1–2 min) into the nucleus (Petrezsélyová et al, ; Roque, Petrezsélyová, Serra‐Cardona, & Ariño, ).…”
Section: The Ena Efflux Systemsupporting
confidence: 70%
“…The promoter region of YPT53 contains a putative calcineurin‐dependent response element (CDRE; consensus sequence: AGCCNC) and a stress‐response element (STRE; AGGGG) 148 and 168 base pairs upstream of the orf. STREs are typically operated by the general stress‐responsive Msn2/4 TFs, but can also be engaged by Gis1 .…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ /CRZ1-Calcineurin/Calmodulin is one of the best studied signaling pathways which provides protection and sensibility for fungal cells against stress conditions. This signaling pathway is already reported to confer Ca 2+ and cell wall stress tolerance in Aspergillus [56], pH responsiveness in S. cerevisiae [57] and it is either related to C. neoformans viability [29,33]. In addition, it is also reported that Ca 2+ supplementation may influence distinct regulatory mechanisms that control holocellulases expression in T. reesei [26].…”
Section: Discussionmentioning
confidence: 84%